PAH/DAS covalently cross-linked layer-by-layer multilayers: a "nano-net" superstratum immobilizes nanoparticles and remains permeable to small molecules1. Issue 34 (14th September 2015) - An, Qi; Nie, Kun; Zhang, Yihe; Wang, Yue; Hu, Yingmo; Dutschk, Victoria; Luan, Xinglong
<x xml:space="preserve">Abstract</x> A "nano-net" superstratum strategy is developed to facilely prepare stabilized layer-by-layer composite films for delayed release up to 55 h.